Electoral coalitions in Matão – effects of change in number of seats on the behavior partisan - Kerbauy, Maria Teresa Miceli (2016)
This article intend to analyze the formation of coalitions between political parties. We seek to verify whether the number of seats (jobs) in dispute affects the behavior of parties in regards to formed coalitions. Therefore, we used as a specific cut out a case study in the city of Matão/SP. The number of openings in dispute differed several times, and political parties have adopted different strategies to achieve the electoral quotient and win representation. We will show that the parties may adapt to the institutional reality in order to use it in their favor, as with the PSL, which reached in 2012 more seats of councilors that bigger and historical parties in this municipality. The table draws for the legislative elections in 2016 brings out a new reduction in the number of seats at stake. It tends to increase electoral competitiveness, which should again influence the behavior of parties.